Antioxidant Activities and Total Phenolics Contents from Extracts of Terminalia catappa, Carrisa carandas, and Opuntia ficus indica Fruits - Ishtiaque, Shagufta; Naz, Shahina; Siddiqi, Rahmanullah; Umer Abdullah, Syed; Khan, Kehkashan; Ahmed, Jawwad; Badaruddin, Muhammad (Recent Innovations in Chemical Engineering, 2014)
To investigate potential sources of the natural antioxidants from fruits, Terminalia catappa, Carissa carandas, and Opuntia ficus indica, have been selected for this study. Their total phenolic content (TPC) and antioxidant activity (AOA) were determined by using DPPH (2,2-diphenyl-1- picrylhydrazyl), ferric reducing power (FRP) and chelating effect methods. Data obtained show that among these species, the highest polyphenolic contents were found in T. catappa (1005 mg/100g GAE) with the highest AOA (49 to 79%), whereas, the least TPC was found in O. ficus indica (200 mg/100g GAE) having AOA (18 to 52%) . However, C. carandas fruit showed moderate polyphenolic content (410 mg/100g GAE) with a significant antioxidant activity (22-64%). On the basis of these results, it has been concluded that antioxidant activity is concentration dependent and TPC of fruits is directly proportional to the antioxidant activities determined by different methods.
Keywords: total phenolic content